Tamanho ótimo de parcela e número de repetições para avaliar a massa de matéria fresca em trigo forrageiro - Bubans, Valéria Escaio (2021)
The objectives of this study was to determine the optimum plot size (Xo) and the number of repetitions to evaluate the mass of fresh matter of forage wheat and to investigate the variability of Xo among agricultural years, sowing dates and cultivars. Thirty-six uniformity trials were conducted (two agricultural years × three sowing dates × two cultivars × three repetitions). The Xo was determined by the method of maximum curvature of the coefficient of variation model, proposed by Paranaíba, Ferreira and Morais (2009a). The number of repetitions was determined for experiments in the completely randomized designs and randomized blocks in scenarios formed by the combinations of i treatments (i=3, 4, …, 50) and d least differences among treatment means to be detected as significant by the Tukey test, at 5% of significance, expressed as a percentage of the overall mean experimental (d=5%, 10%, …, 30%), according to the methodology described in Cargnelutti Filho et at. (2014). The optimum plot size to evaluate the mass of fresh matter of forage wheat is 4.05 m². Seven repetitions are enough to identify the mass of fresh matter in completely randomized designs and randomized block designs up to 50 treatments, making it possible to obtain least significant difference less than or equal to 20% of the average of the experiment.